2013
DOI: 10.1007/s10552-013-0202-4
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of self-reported tobacco use in newly diagnosed cancer patients

Abstract: Purpose Accurate identification of tobacco use is critical to implement evidence-based cessation treatments in cancer patients. The purpose of this study is to evaluate the accuracy of self-reported tobacco use in newly diagnosed cancer patients. Methods Tobacco use questionnaires and blood samples were collected from 233 newly diagnosed cancer patients (77 lung, 77 breast, and 79 prostate cancer). Blood was analyzed for cotinine levels using a commercially available enzyme-linked immunosorbent assay. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
85
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 38 publications
1
85
0
Order By: Relevance
“…Similar to other large population-based surveys of cancer survivors, a limitation is self-report of smoking status and other health-related variables. Self-report of smoking in this study may not be a significant source of bias, however, as a study of newly diagnosed patients with cancer found that self-report of current and never smoking corresponded 100% with cotinine validation (39). In contrast, it was those who self-reported recent quitting within a year for whom there were discrepancies between self-report and biochemical validation; in the current study, however, only 1.2% of respondents reported quitting within a year of our assessment of smoking status.…”
Section: Limitationsmentioning
confidence: 66%
“…Similar to other large population-based surveys of cancer survivors, a limitation is self-report of smoking status and other health-related variables. Self-report of smoking in this study may not be a significant source of bias, however, as a study of newly diagnosed patients with cancer found that self-report of current and never smoking corresponded 100% with cotinine validation (39). In contrast, it was those who self-reported recent quitting within a year for whom there were discrepancies between self-report and biochemical validation; in the current study, however, only 1.2% of respondents reported quitting within a year of our assessment of smoking status.…”
Section: Limitationsmentioning
confidence: 66%
“…This may be because, given the social stigma associated with smoking among head and neck cancer patients, 45 self-reported smoking may be less accurate than biochemically verified smoking status and might introduce misrepresentation of continuing smokers. 8,[45][46][47] However, the misrepresentation of current smokers can be minimized by repeated assessment of self-report smoking status as was done in this and another study conducted with head and neck cancer patients. 45 Several hypotheses have been proposed to explain the relationship between smoking after diagnosis and higher mortality.…”
Section: Discussionmentioning
confidence: 89%
“…First, as in most previous studies, assessments of smoking and alcohol intake were based on participants’ self‐reports. Prior work has shown that self‐reports can often provide an inaccurate assessment of tobacco and alcohol use, particularly in people who have recently been diagnosed with cancer 48. This would most likely result in an underestimation of the effects of smoking and drinking on HNC survival.…”
Section: Discussionmentioning
confidence: 99%